Transcriptome analysis of woodland strawberry (Fragaria vesca) response to the infection by Strawberry vein banding virus (SVBV). Issue 1 (December 2016) - Chen, Jing; Zhang, Hanping; Feng, Mingfeng; Zuo, Dengpan; Hu, Yahui; Jiang, Tong
Abstract Background Woodland strawberry (Fragaria vesca ) infected withStrawberry vein banding virus (SVBV) exhibits chlorotic symptoms along the leaf veins. However, little is known about the molecular mechanism of strawberry disease caused by SVBV. Methods We performed the next-generation sequencing (RNA-Seq) study to identify gene expression changes induced by SVBV in woodland strawberry using mock-inoculated plants as a control. Results Using RNA-Seq, we have identified 36, 850 unigenes, of which 517 were differentially expressed in the virus-infected plants (DEGs). The unigenes were annotated and classified with Gene Ontology (GO), Clusters of Orthologous Group (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The KEGG pathway analysis of these genes suggested that strawberry disease caused by SVBV may affect multiple processes including pigment metabolism, photosynthesis and plant-pathogen interactions. Conclusions Our research provides comprehensive transcriptome information regarding SVBV infection in strawberry.